2018
DOI: 10.2147/vhrm.s166111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular disease among Bangladeshi adult population: a systematic review and meta-analysis of the studies

Abstract: BackgroundCardiovascular disease (CVD) is a group of conditions affecting the functioning of the heart or blood vessels and is one of the leading causes of death globally. Like other countries, CVD prevalence is also rising among the adults in Bangladesh. Epidemiological studies have shown not only a high CVD prevalence but also a significant increase in its prevalence in Bangladesh in the last few decades. To have a better understanding of the current CVD prevalence scenario, we conducted this systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 29 publications
5
52
0
Order By: Relevance
“…The factors behind the increased prevalence of hypertension in the Bangladeshi adult population could be multifarious [13]. In addition to the common risk factors for hypertension such as a high salt intake, being obese, the excessive use of alcohol, physical inactivity, stress, air pollution and smoking [77], other factors including a regional change in disease patterns from communicable to noncommunicable diseases, rapid urbanization, and obsession for embracing western lifestyle could also influence high hypertension prevalence [13,14,78,79]. Fast-Growing unplanned urbanization as seen in developing countries can potentially lead to change in lifestyles (e.g., change in physical activity, diet, environment, and stress) [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors behind the increased prevalence of hypertension in the Bangladeshi adult population could be multifarious [13]. In addition to the common risk factors for hypertension such as a high salt intake, being obese, the excessive use of alcohol, physical inactivity, stress, air pollution and smoking [77], other factors including a regional change in disease patterns from communicable to noncommunicable diseases, rapid urbanization, and obsession for embracing western lifestyle could also influence high hypertension prevalence [13,14,78,79]. Fast-Growing unplanned urbanization as seen in developing countries can potentially lead to change in lifestyles (e.g., change in physical activity, diet, environment, and stress) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Fast-Growing unplanned urbanization as seen in developing countries can potentially lead to change in lifestyles (e.g., change in physical activity, diet, environment, and stress) [13]. In developing countries like Bangladesh, lifestyle, environment, and dietary patterns are quite different in urban and rural areas [14]. These factors are closely linked with a higher prevalence of hypertension and are evident in our study where a higher pooled prevalence of hypertension observed among the urban population (25% compared to 15% in the rural population).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic heart disease (IHD) and stroke are now ranked as the top two causes of Years of Life Lost (YLL) in Bangladesh [5]. A recent systematic review of prevalence studies in Bangladesh reported the overall weighted pooled prevalence of CVD was 5%, regardless of gender, region or type of CVD [6]. The prevalence was found to be higher in urban areas (8% [95% CI: 3-14%]) compared to rural areas (2% [95% CI: 1-4%]) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other countries, cardiovascular disease (CVD) is a progressive reason for increased mortality and services burden in Bangladesh, a developing country with about 160 million of the population as a country experiencing epidemiological transition (13)(14)(15)(16)(17). However, the precise prevalence and risk factors of CVD is yet to be identified (13).…”
Section: Introductionmentioning
confidence: 99%